A Conceptual Framework: The Musical Self as a Unique Pathway to Outcomes in the Acute Pediatric Health Setting. (17th February 2018) - Shoemark, Helen; Rimmer, Jo; Bower, Janeen; Tucquet, Belinda; Miller, Lauren; Fisher, Michelle; Ogburn, Nicholas; Dun, Beth
Abstract: This article reports on a project at the Royal Children's Hospital Melbourne in which the music therapy team synthesized their practice and related theories to propose a new conceptual framework for music therapy in their acute pediatric setting. The impetus for the project was the realization that in the process of producing key statements about the non-musical benefits of music therapy, the cost was often the suppression of information about the patient's unique musical potential as the major (mediating) pathway from referral reason, to music therapy, and to effective outcomes. The purpose of the project was to articulate how this team of clinicians conceive of the patient's musical self as the major theoretical pathway for music therapy in an evidence-based acute medical setting. The clinicians' shared reflexive process across six months involved robust directed discussion, annotation of shared reading, and documentation of all engagement in words and diagrams. The outcome was a consensus framework including three constructs: the place of music in the life of the infant, child, and young people, Culture and Context, and Musical Manifestations. The constructs were tested in a clinical audit, and found to be robustly inclusive. In addition to the conceptual framework, this project serves to demonstrate a process by which clinical teams may reflect on their individual practice and theory together to create a consensus stance for the overall service they provide in the one setting.